Composition of Essential Oil Isolated From Marigold (Tagetes Erecta L.) Flowers Cultivated in Lahore, Pakistan - Ferdosi, Malik Fiaz Hussain; Khan, Iqra Haider; Javaid, Arshad (Bangladesh Journal of Botany, 2022)
The composition of essential oil of marigold (Tagetes erecta L.) flowers was investigated. The oil was analyzed by GC-MS for identification of various components. Among these, 3-cyclohexene-1-methanol, α, α,4-trimethyl-, acetate was the most abundant compound (31.67%) followed by phenol, 2,4-bis (1,1- dimethylethyl)- (14.35%) and eucalyptol (14.27%). Other compounds included dodecanoic acid (5.97%), tetradecanoic acid (5.58%), octadecane (4.93%), propanoic acid, 2-bromo-2-methyl-, ethyl ester (5.43%), cyclohexanol, 1-methyl-4-(1-methylethanyl)-, acetate (5.33), n-hexadecanoic acid (4.70), p-menth-1-en-8-ol (4.20%) and thymol (3.57%). Bangladesh J. Bot. 51(4): 683-688, 2022 (December)